DESKRIPSI KESALAHAN SISWA KELAS XI MIPA SMAN 4 PONTIANAK DALAM MENYELESAIKAN SOAL-SOAL KONSEP MOL - Wulandari, Ranti Indah; Enawaty, Eny; Sartika, Rody Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe background of this research was low student achievement, and there are still many students who had difficulty in solving problems of Â mole concept material. This research was conducted to find out and describe the forms of mistakes made by students of class XI MIPA SMA Negeri 4 Pontianak in solving the problems of the mole concept. The method of this research was descriptive research with a case study form. The subjects in this research were 107 students of class XI MIPA SMA Negeri 4 Pontianak consisting of class XI MIPA 3, XI MIPA 4 and XI MIPA 5. The data collection techniques in this research were measurement techniques, namely through essay diagnostic tests of 5 questions and techniques direct communication that is using unstructured interviews. The results showed that there were 6.34% of students making mistakes in understanding essential concepts; 8.30% of students make mistakes in understanding the relationship between concepts; 16.35% of students make mistakes in understanding the use of a concept to solve a problems.Keywords : Description, Error form, Mole concept